1983
DOI: 10.3109/17453678308992936
|View full text |Cite
|
Sign up to set email alerts
|

Size, Site and Clinical Incidence of Lipoma:Factors in the Differential Diagnosis of Lipoma and Sarcoma

Abstract: All 428 patients who had a non-visceral lipoma histopathologically diagnosed during 1 year in a defined population (0.74 million inhabitants) were analysed retrospectively as regards the age, duration of symptoms, size, site (location and depth) and multiplicity of the lipomas. Solitary subcutaneous lipomas were uncommon in the hand, thigh, lower leg and foot, and four-fifths of them (264/338) were smaller than 5 cm. Multiple subcutaneous lipomas were found in 61 patients, most of them young males. Subfascial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
150
2
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(161 citation statements)
references
References 14 publications
(25 reference statements)
7
150
2
2
Order By: Relevance
“…It is also reported that the intramuscular location of a lipoma is a risk factor for malignancy [1]. In our patient the lesion non infiltrated the muscle planes, but was strictly adhesed to the muscular fascia [3].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is also reported that the intramuscular location of a lipoma is a risk factor for malignancy [1]. In our patient the lesion non infiltrated the muscle planes, but was strictly adhesed to the muscular fascia [3].…”
Section: Discussionsupporting
confidence: 53%
“…Lipomas are the most common benign mesenchymal tumors with a prevalence rate of 2.1 per 1000 people [1]. Lipomas of the neck are rare tumors that may present as slowly growing non-tender masses in the lateral neck.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The variation in site distribution was also observed. Unlike this study, Kransdorf M J et al [7] , Anders Rhydholm and Neil OB [10] and Adair et al [13] reported lipomas mainly on trunk and Jensen O M et al reported on extremity [4] . This may be due to variation in the distribution of adipose tissue in various population.…”
Section: Discussionmentioning
confidence: 51%
“…There was no syndromic association. [5,6] Various studies [7,8,9,10,11] have reported varying incidences of lipoma in their study population 78.7%, 16% , 26.4% , 40% and 37.9% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to distinguish a benign lipoma from a liposarcoma (the most common soft tissue malignancy in adults) may represent a potential medical and legal pitfall (5). Distinguishing a lipoma from a welldifferentiated liposarcoma, however, can represent a unique challenge, but it is highly important due to differences in treatment, prognosis and follow-up (5,6).…”
mentioning
confidence: 99%